2001
DOI: 10.1046/j.1523-1755.2001.00939.x
|View full text |Cite
|
Sign up to set email alerts
|

Nrf2-deficient female mice develop lupus-like autoimmune nephritis11See Editorial by Byrd and Thomas, p. 1606.

Abstract: These data indicate that the aged Nrf2-deficient female mice develop lupus-like autoimmune nephritis and suggest that nrf2 is one of the genes determining susceptibility to autoimmune disease. Analysis of nephritis in the Nrf2-deficient female mouse may clarify the mechanisms leading to the development of lupus disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
244
1

Year Published

2003
2003
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 319 publications
(256 citation statements)
references
References 41 publications
10
244
1
Order By: Relevance
“…Enomoto et al (2001) and Chan et al (2001) clearly demonstrated an enhanced susceptibility to acetaminophen in Nrf2-deficient mice. We also reported that Nrf2 female mice developed autoimmune glomerulonephritis probably due to susceptibility to oxidative stress (Yoh et al, 2001). In addition, Ramos-Gomez et al (2001) showed that Nrf2 was central to the constitutive and inducible expression of phase two enzymes in vivo and dramatically influences susceptibility to carcinogens.…”
Section: Nrf2 and Death Signals N Morito Et Almentioning
confidence: 82%
“…Enomoto et al (2001) and Chan et al (2001) clearly demonstrated an enhanced susceptibility to acetaminophen in Nrf2-deficient mice. We also reported that Nrf2 female mice developed autoimmune glomerulonephritis probably due to susceptibility to oxidative stress (Yoh et al, 2001). In addition, Ramos-Gomez et al (2001) showed that Nrf2 was central to the constitutive and inducible expression of phase two enzymes in vivo and dramatically influences susceptibility to carcinogens.…”
Section: Nrf2 and Death Signals N Morito Et Almentioning
confidence: 82%
“…Female Nrf2-deficient mice develop a lupus-like immune-complex disease as they age, characterized by anti-nuclear autoantibodies and glomerulonephritis [9,10]. In these models, Nrf2-deficient animals show increased indices of oxidant stress, decreased antioxidant capacity, and less activation of antioxidant genes than Nrf2-intact mice [5,6,[9][10][11]. Taken together, these data suggest that Nrf2-dependent genes play a role in suppressing inflammation and maintaining immune tolerance.…”
Section: Introductionmentioning
confidence: 85%
“…Mice deficient in Nrf2 display significantly more pulmonary inflammation in hyperoxic and bleomycin-induced lung injury compared to wild-type animals [5,6], and demonstrate prolonged inflammation during cutaneous wound healing [7] and carrageenan-induced pleurisy [8]. Female Nrf2-deficient mice develop a lupus-like immune-complex disease as they age, characterized by anti-nuclear autoantibodies and glomerulonephritis [9,10]. In these models, Nrf2-deficient animals show increased indices of oxidant stress, decreased antioxidant capacity, and less activation of antioxidant genes than Nrf2-intact mice [5,6,[9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to its role in regulating ROS levels, several recent studies have showed that the Nrf2 pathway regulates immune and inflammatory processes. Yoh et al (2001) reported that Nrf2-deficient female mice developed lupus-like autoimmune nephritis. It was also demonstrated that Nrf2-deficient mice exhibit prolonged inflammation during cutaneous wound healing and display enhanced bronchial inflammation and susceptibility to cigarette smoke-induced emphysema (Iizuka et al 2005).…”
Section: Discussionmentioning
confidence: 99%